(untitled) (Journal of Fiber Bioengineering and Informatics, 2010)
Today, many photosensitive polyimide (PI) materials are studied for their excellent thermo mechanical, low dielectric constants and high dissipation factors. Hence, two hemicyanine dyes, named DHEASP Br-C_4, and DHEASP Br-C_8, were synthesized in this paper and were incorporated by doping with polyamic acid (PAA) in N, N-dimethylacetamide (DMA) solution to obtain fluorescent PI nanofibers. Firstly, PAA nanofibers were achieved using electrospinning process (ESP) at room temperature. 4 hours later, polyimide (PI) nanofibers were successfully obtained by thermal imidization in vacuum oven while the temperature was 200°C and vacuum degree was 133 Pa. Results show that one-photon emission fluorescence peaks of two hemicyanine dyes in N, N-dimethylformamide (DMF) solution was located at 606 nm and 613 nm respectively, while all mats that consisted of those PPA nanofibers, or PI nanofibers showed good fluorescent properties and their one-photon emission fluorescence spectra were located around 600 nm. Hence, nanofluorescent PI fibers can be prepared by electrospinning technique.